Predictors Of Antiretroviral Therapy Failure In HIV/AIDS Patients At Dr. Moewardi Regional Hospital, Surakarta - Fachry Harbipero; Niken Luthfiyanti; Vivin Marwiyati (International Journal of Health Engineering and Technology, 2026)
Antiretroviral (ARV) therapy failure remains a significant issue in HIV/AIDS control as it contributes to disease progression and drug resistance. This study aims to analyze predictors of ARV therapy failure based on demographic and clinical characteristics of HIV/AIDS patients. This study used a retrospective quantitative descriptive analytical design with medical records of HIV outpatients at Dr. Moewardi Regional General Hospital from November 2024 to November 2025 as the data source. The study population was all HIV patients receiving ARV therapy, with a sample of 100 patients selected using accidental sampling. The research instrument was a medical record-based observation sheet, covering demographic, clinical, CD4, viral load, and clinical stage characteristics. Data analysis was performed univariately and bivariately using the Chi-square test with a significance level of p<0.05. The results showed that the majority of patients were male, productive age, married, had secondary or higher education, had a normal BMI, were in the early clinical stage, and did not experience opportunistic infections or side effects of therapy. No significant associations were found between demographic and clinical variables and CD4 count, viral load, or clinical stage. In conclusion, the immunological, virological, and clinical status of HIV patients is multifactorial and is not solely determined by the demographic and clinical characteristics studied.